Beyond necessity and opportunity entrepreneurship: Understanding the motivations behind gluten-free home-based businesses in Saudi Arabia - Alabdelmuhsin, Bshaar (2019)
When discussing entrepreneurs’ motivations for starting their businesses, it has become common to classify them as either push/necessity or pull/opportunity factors. This simplistic bifurcated depiction has also been widely used by the literature to explain the motives of informal entrepreneurs. For decades, there has been a widely held assumption that informal entrepreneurs operate in the informal economy out of economic necessity to survive, as a last resort in the absence of alternatives. This study evaluates critically this dichotomous representation of informal entrepreneurs’ motives through an examination of the motivations behind gluten-free home-based businesses (GFHBBs) in Saudi Arabia (SA). The majority of HBBs in SA are owned by women entrepreneurs but until now, no studies have sought to understand Saudi women’s motivations for operating in the informal economy in general, and in GFHBBs in particular. This study aims to fill this gap.